Diversity of chemical composition among seed oils obtained from different grape varieties - Dabetić, Nevena; Todorović, Vanja; Zrnić Ćirić, Milica; Djuričić, Ivana; Šobajić, Sladjana (Archives of Pharmacy, 2022)
Wine industry generates enormous quantities of solid organic waste consisted of stems, skins and seeds. Grape seeds are considered the most valuable part of a pomace, since it is rich in oil and containing numerous bioactive compounds. Grape seed oil (GSO) composition depends mainly on grape variety, but also on environmental factors and maturation degree. The aim of this study was to investigate the diversity of chemical composition among seed oils obtained from different grape varieties. Eight varieties were collected from the same wine region and at the same maturity phase. Investigation of fatty acid composition was done using GC/FID, while HPLC/FD was employed for vitamin E analyses. Linoleic acid was the most abundant in all samples, followed by oleic acid. Saturated fatty acids, such as palmitic and stearic acid, were also present (up to 20 % of the total fatty acid methyl esters). Vitamin E concentrations were significantly affected by grape variety (p<0.01). α-tocopherol was found in high concentration in all samples. GSO from Shiraz variety had about 25 mg α-tocopherol per kg of oil, while Gamay GSO contained more than six times less amounts of this vitamin E isoform. Sum of β and γ tocopherol also varied considerable, although Shiraz again stood out with the highest content. Finally, δ tocopherol was found in four varieties, in minor quantities. Generally, considering variety diversification on vitamin E composition of GSO, investigations that will include as much varieties as possible, are needed to single out ones with the highest bio-oil potential.